GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 14 Oct 2019, 04:36 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

Hide Tags

Manager  S
Joined: 26 Nov 2018
Posts: 96
Concentration: Technology, Entrepreneurship
GPA: 3.3
WE: Manufacturing and Production (Manufacturing)
If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the  [#permalink]

Show Tags

4 00:00

Difficulty:   45% (medium)

Question Stats: 63% (01:41) correct 37% (02:20) wrong based on 41 sessions

HideShow timer Statistics

If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the value of f(8)?

A. 2
B. 3
C. 4
D. 5
E. 6

Originally posted by Rashed12 on 04 Mar 2019, 07:41.
Last edited by Bunuel on 04 Mar 2019, 07:43, edited 1 time in total.
Renamed the topic and edited the question.
CEO  V
Joined: 12 Sep 2015
Posts: 3990
Re: If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the  [#permalink]

Show Tags

1
Top Contributor
Rashed12 wrote:
If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the value of f(8)?

A. 2
B. 3
C. 4
D. 5
E. 6

Given: f(n + 3) = f(n)
So, for example, f(1 + 3) = f(1)
In other words, f(4) = f(1)

Likewise, f(5) = f(2)
And f(6) = f(3)
And f(7) = f(4)
And f(8) = f(5)
etc

ASIDE: Notice that -1 + 3 + 3 + 3 = 8
So, f(-1) = f(2) = f(5) = f(8)
We're told that f(-1) = 6, so it must also be the case that f(2) = 6, f(5) = 6, and f(8) = 6

Cheers,
Brent
_________________
Senior Manager  P
Status: Whatever it takes!
Joined: 10 Oct 2018
Posts: 381
GPA: 4
Re: If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the  [#permalink]

Show Tags

Rashed12 wrote:
If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the value of f(8)?

A. 2
B. 3
C. 4
D. 5
E. 6

f(-1) = 6, f(0) = 5, f(1) = 4 and f(n + 3) = f(n). By using all these information, we need to find f(8).

n=-1 => f(-1+3)=f(-1) => f(2)= f(-1) => f(2)=6

n=0 => f(0+3)=f(0) =>f(3)=5

Similarly,
When n=1, f(4)=4
n=2, f(5)=6
n=3, f(6)=5
n=4, f(7)=4
n=5, f(8)=6

Note: After f(5), you can notice the trend in answers. From f(2) the answers are 6, 5, 4, 6..... so by counting the rest based on this trend, you can find the answer for f(8).

Anyways, the answer is option E.
_________________

ALL ABOUT GMAT- \(https://exampal.com/gmat/blog/gmat-score-explained\)
Intern  B
Joined: 26 Mar 2018
Posts: 14
Re: If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the  [#permalink]

Show Tags

Rashed12 wrote:
If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the value of f(8)?

A. 2
B. 3
C. 4
D. 5
E. 6

f(n+3)=f(n)
f(8)=f(5+3)=f(5)
f(2+3)=f(2)
f(-1+3)=f(-1)
and it's given that f(-1)=6
So, answer is E Re: If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the   [#permalink] 23 Mar 2019, 09:37
Display posts from previous: Sort by

If f(n + 3) = f(n) and f(-1) = 6, f(0) = 5, f(1) = 4, then what is the

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne  